Dropping the debt: a new conundrum in Kant's rational religion - Clem, Stewart ca. 20./21. Jh. (Religious studies, 2018)
In this article, I argue that Immanuel Kant fails to provide a satisfactory account of moral debt' in Religion within the Boundaries of Mere Reason. More precisely, he fails to answer the question of why we should assume that a debt exists in the first place. In light of recent scholarship on this area of his thought, I sketch some possible readings of Kant on the nature of moral transformation that suggest how he might account for this debt. I then argue that these accounts fail to justify its existence within Kant's project.